Risk Management and Insurance - Nguyen, Xuan Tiep (Khoa Quốc tế, ĐHQGHN, 2020)
The course is to advance student understanding of how to use financial information to value and analyze risks involved to firms business, as well as how to define strategies relevant to each category of risk to keep them under close control. We will apply your economics, accounting, finance skills to problems from today's business news to help us understand what is contained in financial reports, why firms report certain information, and how to be a sophisticated user of this information.